2016
DOI: 10.4188/jte.62.123
|View full text |Cite
|
Sign up to set email alerts
|

Relating Self-assembly to Spatio-temporal Keratin Expression in the Wool Follicle

Abstract: Two of the present authors have presented a model for macrofibril template self-assembly which is based on a concerted process of sudden, delayed, short filament formation with immediate phase transfer to a lyotropic liquid crystal (mesophase). In recent years, information on the spatio-temporal patterns of keratin protein expression within wool follicles has come to hand, and we here report some recently acquired important information in this area. If the "mesophase model" is to remain credible it must be com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As an explanation of proto‐MF formation in cortical cells, a mesophase (lyotropic liquid crystal) separation model has been proposed from detailed TEM data and thermodynamic theories [26,34,35]. In this model, the abundant hair keratin pair, K85 and K31, builds up a high concentration of ULFs in the lower cortex cells, and any further lengthening of the ULFs into short IFs will quickly result in the formation of a concentrated oriented phase, the mesophase, appearing initially as spindle‐shaped tactoids, i.e., early‐stage proto‐MFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an explanation of proto‐MF formation in cortical cells, a mesophase (lyotropic liquid crystal) separation model has been proposed from detailed TEM data and thermodynamic theories [26,34,35]. In this model, the abundant hair keratin pair, K85 and K31, builds up a high concentration of ULFs in the lower cortex cells, and any further lengthening of the ULFs into short IFs will quickly result in the formation of a concentrated oriented phase, the mesophase, appearing initially as spindle‐shaped tactoids, i.e., early‐stage proto‐MFs.…”
Section: Discussionmentioning
confidence: 99%
“…In the cortex of a hair or wool fiber, hair keratin IFs are arrayed into bundles, in which each IF is surrounded by a matrix material composed of keratinassociated proteins (KAPs) [3,4,[24][25][26]. The supramolecular structures organized by hair keratin IF bundles and KAPs, termed macrofibrils (MFs), have a diameter of 200-500 nm and a maximum length of ~10 µm and fill the cortex by lateral and longitudinal assembly along the fiber [4,17,[25][26][27][28][29][30][31][32][33][34][35][36][37]. Transmission electron microscopy (TEM) studies of MF formation have revealed the appearance of hair keratin IF bundles in the lower cortex, i.e., proto-macrofibril (proto-MFs) with a width of 50-100 nm and a length of several hundred nanometers, some of which are attached to a desmosome, while others are isolated in the cytoplasm [4,26,28,30,31,34,35,37].…”
mentioning
confidence: 99%
“…Nuclear DNA is degraded as cells move away from the bulb . Early observations have recently been validated using modern microscopy methods, which, along with live cell imaging of bulb cortical cells, suggests nuclear degradation begins well before the top of the DP.…”
Section: Biology and Chemistry: Proliferation Differentiation And Shafmentioning
confidence: 97%
“…Cortical keratins appear in the cytoplasm beginning at Auber's line (first K35, and K85, and then K31) . Keratin structures first appear a few cell lengths distal of the onset of K31 expression . These first structures are dense aggregations of intermediate filaments (IFs) and can be associated with desmosomes or be cytoplasmic .…”
Section: Biology and Chemistry: Proliferation Differentiation And Shafmentioning
confidence: 99%
See 1 more Smart Citation